Immobilisation of anthocyanin in starch-based film as a potential colorimetric oxygen indicator in modified atmosphere condition - Che Hamzah, Nurul Husna; Khairuddin, Nozieana; Muhamad, Ida Idayu (HH Publisher, 2024)
Modern food packaging implies modified atmosphere packaging (MAP) to prolong the shelf life of food. Certain foods need oxygen such as meat (myoglobin) red colour. Recently, colourimetric oxygen indicator has been beneficial to be applied in food packaging because it can be used to monitor the oxidation in the headspace of MA packaging). Anthocyanin pigments are sensitive to gases. In this study, different concentration of red cabbage anthocyanin (RCA) was incorporated in sago starch formulations to produce an oxygen indicator film. A modified atmosphere environment was set up by using a desiccator connected to a vacuum pump to remove the oxygen gas until the required level (10%). The oxygen level was monitored using an oxygen meter. It was observed that the films were able to be used for oxidation process detection since the anthocyanin changed its original purple colour to brown once it was exposed to the oxygen, whereas the original colour of the films can be preserved in a modified oxygen atmosphere which has an oxygen content of less than 10%. The colour properties of the indicator films were recorded using the CIELAB scale (L*, a*, b*) which signifies lightness, rednessgreenness, and yellowness-blueness, respectively. A film with 12% w/v RCA showed the highest colour lightness transition in a modified oxygen atmosphere (1.63%) whereas the 8% w/v RCA film showed the highest lightness transition in normal oxygen conditions (2.25%). The prepared oxygen indicator film was able to provide visual support to judge whether there is an oxidation process that has occurred in the food packaging closed system.